2015
DOI: 10.1120/jacmp.v16i5.5302
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography dosimetry with high‐resolution detectors commonly used in radiotherapy — an energy dependence study

Abstract: New methods of dosimetry in computed tomography (CT) X‐ray fields require the use of high‐resolution detectors instead of pencil‐type ionization chambers typically used for CT dose index (CTDI) measurements. This paper presents a study on the suitability of a wide range of ionization chambers, diodes, and a two‐dimensional detector array, used primarily in radiation therapy, for CT and cone‐beam CT dosimetry. Specifically, the energy dependence of these detectors from 50 kVp up to 125 kVp is reported. All meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Liebmann et al. reported an energy response variation of 4.5% for the Pinpoint chamber (PTW 31014) in water over the energy range of 50–125 kV 32 which this study extends upon to include 200 kV and 6 MV. Snow et al.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Liebmann et al. reported an energy response variation of 4.5% for the Pinpoint chamber (PTW 31014) in water over the energy range of 50–125 kV 32 which this study extends upon to include 200 kV and 6 MV. Snow et al.…”
Section: Discussionmentioning
confidence: 50%
“…The difference in response is attributed to the amount of aluminum in the Farmer inner central electrode that makes it more susceptible to over-respond to low-energy photons. Liebmann et al reported an energy response variation of 4.5% for the Pinpoint chamber (PTW 31014) in water over the energy range of 50-125 kV 32 which this study extends upon to include 200 kV and 6 MV. Snow et alexamined the change in air-kerma calibration coefficients as a function of photon energy, and between 100 and 250 kV, the Farmer-type chambers in the study displayed a variation of up to 14% when used during negative charge collection but less than 5% during positive charge collection.…”
Section: Detector Energy Dependencementioning
confidence: 50%